Effect of vasopressin on a porcine model of persistent pulmonary hypertension of the newborn. Issue 3 (15th January 2019) - Amer, Reem; Elsayed, Yasser N.; Graham, Marjory Ruth; Sikarwar, Anurag S.; Hinton, Martha; Dakshinamurti, Shyamala
Abstract: Background: Persistent pulmonary hypertension of the newborn (PPHN) is due to a failure of pulmonary vascular relaxation. Vasopressin, a systemic vasoconstrictor acting on smooth muscle AVPR1a receptors, is used in treatment of PPHN. We sought to determine acute effects of vasopressin infusion on pulmonary hemodynamics in a large animal model of hypoxic PPHN. Methods: PPHN was induced in 6 newborn piglets by 72 h normobaric hypoxia (FiO2 = 0.10); controls were 7 age‐matched 3‐day‐old piglets. Animals were anesthetized and ventilated with central venous and arterial lines, and after stabilization, randomized using a crossover design to normoxic or hypoxic ventilation, then 30 min infusion of 0.0012 U/kg/min vasopressin, followed by 45 min vasopressin washout period. Echocardiographic parameters and oxygen consumption were measured before and after vasopressin. Relaxation to vasopressin was tested in isolated PPHN and control pulmonary arteries by isometric myography. Expression of AVPR1a receptor mRNA was quantified in arterial and myocardial tissues. Results: Vasopressin did not alleviate hypoxia‐responsiveness of PPHN pulmonary circuit. There were no significant differences in pulmonary hypertension, cardiac function indices, or oxygenation indices after vasopressin infusion. Vasopressin did not dilate control or PPHN pulmonary arteries, and AVPR1 was minimally expressed. Conclusions: Vasopressin does not have a direct pulmonary vasodilator effect in PPHN, within the timeframe studied.